Targeting IL-13 as a Host-Directed Therapy Against Ulcerative Colitis - Hoving, J. Claire (Frontiers in Cellular and Infection Microbiology, 2018)
The role of interleukin-13 in mediating ulcerative colitis remains under scrutiny. Compelling evidence from both man and mouse suggests that IL-13 not only contributes to the pathology associated with disease but is also involved in mediating the inflammatory response. These studies have led to the approach of targeting IL-13 as a promising treatment strategy in alleviating ulcerative colitis disease. Despite this evidence, recent clinical trial data suggests that specifically blocking the receptor through which IL-13 signals, IL-4 receptor-alpha (IL-4Rα) in ulcerative colitis patients, is insufficient in protecting them from disease outcome. This challenges the importance of IL-13 as a therapeutic target. This review describes the role of IL-13 in ulcerative colitis and current treatment strategies that target IL-13. The potential role of IL-13 signalling independently of IL-4Rα in mediating ulcerative colitis is highlighted as an important consideration when targeting the signalling mechanisms of IL-13 for therapeutic approaches.